Lublin Metropolitan Area in Terms of Spatial Planning - Waldemar Gorzym-Wilkowski (Barometr Regionalny, 2013)
The metropolitan area in Polish literature is generally understood as a large city with its functionally related vicinity. The Lublin Metropolitan Area (LOM) was identified in 2011 as one among 10 such areas in Poland by the government’s country spatial development concept. The concept envisages that metropolitan areas are to be supported, first of all, to improve their competitiveness, by governmental investment projects and the improvement in the functioning of public institutions. Spatial planning for Lubelskie voivodship, on the other hand, declares the need to shape LOM through numerous investment, protective, institutional and organizational activities. However, governmental and voivodship spatial planning has limited possibilities to implement its determinations. Especially the implementation of determinations concerning organizational and institutional solutions and, to a certain extent, also investment projects remains to a large degree beyond the competences of spatial planning entities. As a result, spatial planning, being the main plane of interest in the functioning of LOM on the pary of public authorities, may effectively impact the development and directions in transformations of this area only to a small degree.